Perbandingan Kinerja Generalized Frequency Division Multiplexing Menggunakan Modulasi QAM dan Offset QAM - Ari Endang Jayati; Budiani Destyningtias (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2023)
Generalized frequency division multiplexing (GFDM) is a future nonorthogonal multicarrier system. GFDM is a block-shaped data transmission technique in which each subcarrier is formed from nonrectangular shaped pulses. The application of quadrature amplitude modulation (QAM) mapping for GFDM is excellent because of the increased spectral efficiency. QAM also has limitations, namely increasing complexity when implemented. Apart from that, the inter carrier interference (ICI) persists and greatly influences the system. The technique for mitigating this weakness is by using offset QAM (OQAM) mapping. The advantages of GFDM/OQAM over GFDM/QAM are that the quadrature and in-phase components in OQAM modulation do not experience shifts in the same time slot, low out of band (OOB), high data rate and is ICI free. This study compares two scenarios namely the GFDM/OQAM and the GFDM/QAM systems. It analyzes the performance of the bit error rate (BER) if additive white gaussian noise (AWGN) and Rayleigh channels are passed. The simulation results show that GFDM/OQAM has better performance results. The simulation results showed that in order to obtain BER 10-2, there should be a decrease in the value of Eb/N0 (ratio of energy per bit to noise power) by 8 dB in QAM to OQAM when they were passed AWGN channels. Meanwhile, when passed the Rayleigh Fading channel, there was a decrease in the Eb/N0 value by 9 dB in the QAM to OQAM to get a BER value of 10-2. This study has also succeeded in investigating the performance of the two systems for parameters of the constellation diagram and signal spectrum. Moreover, it has succeeded in obtaining a roll off factor reference value that can be used in the application of the GFDM/OQAM system with the best performance result of 0.3. The roll off factor value greatly affects the performance of the GFDM system.